A mutagenomic dissection of virulence in the fungal wheat pathogen Zymoseptoria tritici - Blyth, Hannah R. (2022)
Zymoseptoria tritici is the causal agent of Septoria tritici leaf blotch (STB), an economically significant disease that can reduce wheat (Triticum aestivum) yields. Due to this fungus' in vitro growth capabilities, functional genomics studies can isolate morphogenic switching genes that play a crucial role in fungal virulence. Depending on in vitro nutrient availability and temperature, Z. tritici can grow and switch between a “yeast-like” budding form or a hyphal form. As no specialised infection structures have been identified in Z. tritici infection, the genes involved in morphogenic switching and successful hyphal extension are essential for virulence, enabling leaf penetration through stomatal openings or wounds. “Mutagenomics” is a combination approach of mutagenesis, phenotypic screening, and whole-genome re-sequencing. Advancements in genomic sequencing technologies have eased the process of identifying candidate virulence and morphogenic switching associated genes in Z. tritici.